(untitled) (Al-Muthanna Journal of Sport Education Sciences, 2026)
Using specific exercises that closely resemble real-world drills in teaching the technical performance of the hammer throw to beginner students raises their technical level, enabling them to achieve high marks in both the practical and theoretical aspects of the sport. The importance of this approach lies in incorporating these specific arm exercises into the learning of the technical performance of the hammer throw, This is useful for beginner students, track and field instructors in physical education and sports science departments, and those working in the field of teaching and training beginners and new trainees, as it can help in mastering this activity when learning it, The problem with this study is the scarcity of research on this activity, both nationally and internationally. Consequently, students lack some of the necessary skills and abilities, leading to poor performance in areas such as hammer throw distance, Similarly, their arm strength is assessed through arm strength tests and performance evaluations after receiving instruction on hammer throwing techniques and understanding its movement path. Ultimately, they need to improve their throwing skills, This leads to better performance and greater success. The purpose of the study is to develop specific arm exercises using static and dynamic muscle work with new equipment to enhance certain physical capabilities of the arms (endurance, grip strength, etc.) and to determine their impact on learning the technical performance of the hammer throw, This study was conducted for beginner students in the third year of the College of Physical Education and Sports Sciences, aiming to determine the effect of these specific exercises and the differences between the two groups (control and experimental) on the studied variables. The research population consisted of a group of beginner students in the third year of the College of Physical Education and Sports Sciences at Al-Qadisiyah University for the academic year (2024-2025), The sample consisted of (108) students who had never previously learned the technical performance of the hammer throw. Two sections, (C) and (D), were randomly selected, totaling (59) students. The research sample comprised (52) students, representing (48.148%) of the research population, after excluding (7) students who did not attend regularly, They were divided into two groups,with (26) students in one group. The sample as a whole was homogeneous and the two groups were equivalent. All field procedures were implemented, the educational curriculum design (special arm exercises), The study focused on the technical performance of the hammer throw, the necessary data was collected, appropriate statistics were compiled and tabulated, analyzed, discussed, and conclusions and recommendations were drawn from the results achieved.